Bifurcation Structure in a Bimodal Piecewise Linear Business Cycle Model - Viktor Avrutin; Iryna Sushko; Fabio Tramontana (Abstract and Applied Analysis)
We study the bifurcation structure of the parameter space of a 1D continuous piecewise linear bimodal map which describes dynamics of a business cycle model introduced by Day-Shafer. In particular, we obtain the analytical expression of the boundaries of several periodicity regions associated with attracting cycles of the map (principal cycles and related fin structure). By crossing these boundaries the map displays robust chaos.